How influencers and digital interaction can impact customer-brand relationship and engagement - Bilro, R. G.; Loureiro, S. M. C.; Guerreiro, J.; Raposo, D. (2020 Global Marketing Conference at Seoul Proceedings, 2020)
This research seeks to unveil how YouTube influencers and digital interaction can contribute to the process of customer-brand relationship and engagement. Based on in-depth interviews of female Youtubers devoted to the lifestyle categories, we aim to comprehend the engagement factors that influencers should rely on to promote engagement between their followers and the brands they advocate.